25‐Hydroxycholesterol amplifies microglial IL‐1beta production in an APOE isoform‐dependent manner: Lipids in AD and FTD: From genes to interventions. (7th December 2020) - Wong, Man Ying; Lewis, Michael; Doherty, Jim; Shi, Yang; Gong, Shiaoching; Qian, Mingxing; Cashikar, Anil G.; Sullivan, Patrick M.; Petsko, Gregory A.; Covey, Douglas; Gan, Li; Holtzman, David M.; et al.
Abstract: Background: Genome‐wide association studies of Alzheimer's disease (AD) have implicated pathways related to lipid homeostasis and innate immunity in AD pathophysiology. However, the exact cellular and chemical mediators of neuroinflammation in AD remain poorly understood. The oxysterol 25‐hydroxycholesterol (25‐HC) is an important immunomodulator produced by peripheral macrophages with wide‐ranging effects on cell signaling and innate immunity. Genetic variants of the enzyme responsible for 25‐HC production, cholesterol 25‐hydroxylase (CH25H), have been found to be associated with AD. Method: In the present study, we measured CH25H expression in human AD brain and AD transgenic mouse brains. We also investigated the activity of 25‐HC in LPS‐induced innate immune responses including cytokine production in primary mouse microglia and human iPSC‐derived microglia‐like cells. Results: we found that CH25H expression is upregulated in human AD brain tissue and in transgenic mouse brain tissue bearing amyloid‐bplaques or tau pathology. Treatment with the toll‐like receptor 4 (TLR4) agonist lipopolysaccharide (LPS) markedly upregulates CH25H expression in the mouse brain and stimulates CH25H expression and 25‐HC secretion in mouse primary microglia. We found that LPS‐induced microglial production of the pro‐inflammatory cytokine IL‐1bis markedly potentiated by 25‐HC and attenuated by deletion of CH25H.The upregulation of LPS‐induced IL‐1bby 25‐HC was validated in human microglia‐like cells derived from iPSCs. Through a 42‐multiplex human cytokine assay, we further found that 25‐HC specifically induces IL‐1beta and IL‐1alpha, with little effects on other cytokines in human microglia‐like cells. Interestingly, microglia expressing apolipoprotein E4 (apoE4), a genetic risk factor for AD, produce greater amounts of 25‐HC than apoE3‐expressing microglia following treatment with LPS. Remarkably, 25‐HC treatment results in a greater level of IL‐1bsecretion in LPS‐activated apoE4‐expressing microglia than in apoE2‐ or apoE3‐expressing microglia. Blocking potassium efflux or inhibiting caspase‐1 prevents 25‐HC‐potentiated IL‐1brelease in apoE4‐expressing microglia, indicating the involvement of caspase‐1/NLRP3 inflammasome activity. Conclusion: 25‐HC may function as a microglial secreted inflammatory mediator in brain, promoting IL‐1b‐mediated neuroinflammation in an apoE isoform‐dependent manner (E4>>E2/E3) and thus may be an important mediator of neuroinflammation in AD.